2015
DOI: 10.5194/acp-15-1013-2015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation slopes of GEM / CO, GEM / CO<sub>2</sub>, and GEM / CH<sub>4</sub> and estimated mercury emissions in China, South Asia, the Indochinese Peninsula, and Central Asia derived from observations in northwestern and southwestern China

Abstract: Abstract. Correlation analyses between atmospheric mercury (Hg) and other trace gases are useful for identification of sources and constraining regional Hg emissions. Emissions of Hg in Asia contribute significantly to the global budget of atmospheric Hg. However, due to the lack of reliable data on the source strength, large uncertainties remain in the emission inventories of Hg in Asia. In the present study, we calculated the correlation slopes of GEM / CO, GEM / CO 2 , and GEM / CH 4 for mainland China, Sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 86 publications
2
23
0
1
Order By: Relevance
“…4). Openpath pulsed laser optical spectroscopic (LIDAR) method and Hg 0 / CO ratio were applied to estimate Hg emission from area/regional sources (e.g., LIDAR: mining areas, industrial plants, geothermal sites; Hg 0 / CO ratio: continental level atmospheric Hg transport) (Aldén et al, 1982;Edner et al, 1991;Sjöholm et al, 2004;Jaffe et al, 2005;Fu et al, 2015a). There has not been a standardized protocol for any of the techniques (e.g., instrumentation set-up, operation parameters) (Gustin, 2011;Zhu et al, 2015b).…”
Section: Advances In Hg 0 Flux Quantification Methodsmentioning
confidence: 99%
“…4). Openpath pulsed laser optical spectroscopic (LIDAR) method and Hg 0 / CO ratio were applied to estimate Hg emission from area/regional sources (e.g., LIDAR: mining areas, industrial plants, geothermal sites; Hg 0 / CO ratio: continental level atmospheric Hg transport) (Aldén et al, 1982;Edner et al, 1991;Sjöholm et al, 2004;Jaffe et al, 2005;Fu et al, 2015a). There has not been a standardized protocol for any of the techniques (e.g., instrumentation set-up, operation parameters) (Gustin, 2011;Zhu et al, 2015b).…”
Section: Advances In Hg 0 Flux Quantification Methodsmentioning
confidence: 99%
“…These areas are regarded as important source regions of many air pollutants that pose significant health risks locally and regionally (Rajgopal, 2003;Lelieveld et al, 2001). Previous studies indicated that Hg emissions within south and southeast Asia, including southwestern China, have significant impacts on the distribution and deposition of atmospheric Hg in south and east Asia Mukherjee et al, 2009;Sheu et al, 2013;Fu et al, 2015;Zhang et al, 2012). These influences have raised concerns about high atmospheric Hg levels in India and southwestern China, and increased Hg contents in the snow packs of Hindu Kush Himalayan-Tibetan glaciers (Loewen et al, 2005(Loewen et al, , 2007Kang et al, 2016).…”
mentioning
confidence: 99%
“…Recent studies revealed that Hg emissions from anthropogenic and natural sources in China were in the range of 800-1200 t (Shetty et al, 2008; S. X. Fu et al, 2015a;Wang et al, 2016), approximately 1/6 of the global Hg emissions into the atmosphere Song et al, 2015). The large emissions in China not only have an impact on the domestic Hg pollution (Fu et al, 2015b), but also have the potential to enhance atmospheric Hg concentration and deposition elsewhere (Seigneur et al, 2004;Strode et al, 2008;Durnford et al, 2010).…”
Section: Introductionmentioning
confidence: 99%